Prevention of ethanol and aspirin-induced gastric mucosal lesions by paracetamol and salicylate in rats: role of endogenous prostaglandins. Issue 6 (June 1982) - Konturek, S J; Brzozowski, T; Piastucki, I; Radecki, T
Abstract : Paracetamol or sodium salicylate given intragastrically 30 minutes before the administration of absolute ethanol or acidified aspirin dose-dependently reduced the formation of mucosal lesions. The generation of gastric mucosal prostaglandin-like activity increased with ethanol and was completely suppressed by acidified aspirin. Paracetamol or sodium salicylate given alone increased the generation of mucosal prostaglandin-like material. Indomethacin, the prostaglandin synthesis inhibitor, suppressed this effect and inhibited the protective influence of paracetamol or sodium salicylate on the production of gastric lesions.